F FORMULATION DEVELOPMENT AND EVALUATION OF CARBOPOL-INCORPORATED THERMOREVERSIBLE GELS OF PSEUDOEPHEDRINE FOR RECTAL DRUG DELIVERY: Formulation and Evaluation of Thermoreversible gels of Pseudoephedrine - FIROZ S; PADMINI K; PADMASREE K; SRAVANI N; HEMALATHA A; VENNELARANI Y (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The present study describes the preparation and evaluation of a Poloxamer 188 (P188)-based thermoreversible gel using Carbopol 934P (C934P) as a mucoadhesive polymer of pseudoephedrine for enhancing the bioavailability and to avoid the first-pass metabolism. Materials and Methods: Five formulations (F1-F5) were prepared using cold method. The prepared gels were characterized by pH, drug content, spreadability, mucoadhesive force, gelation temperature, and drug release profile. Thermoreversibility of P188/C934P gel was demonstrated by rheological studies. The drug-polymer compatibility was studied using Fourier transform infrared (FTIR). Results: The incorporation of carbopol into P188 gel also reduced the amounts of drug released from the gel formulations. FT-IR studies revealed that there are no interactions between the drug and polymers. Drug content of gels was estimated and the results were found to be satisfactory. In vitro dissolution studies revealed a good drug release from the gels. The drug release was higher in formulations F4 and F5 and lower in F1, F2, and F3 formulations. The order of drug release was found to be F5>F4>F3>F2>F1. Conclusion: These findings suggested that developed thermoreversible gels could be used as promising dosage forms to rectal drug delivery for prolonged periods in the management of hemorrhoids.